Policy Evaluation of Cikudul Simple Rental Flat (RUSUNAWA) Program in Sukabumi City - Ratna Nabillah; M. Rijal Amirulloh; Rizki Hegia Sampurna (Dinasti International Journal of Education Management And Social Science, 2024)
The phenomenon of rapid urbanization in Sukabumi triggers the need for decent housing for low-income people (MBR). This study aims to evaluate the policy of the Cikudul Simple Rental Flat (RUSUNAWA) Program in Sukabumi City. The research method used is qualitative with data collection techniques through observation, interviews, and documentation. The results showed that although RUSUNAWA was available, there were still obstacles in physical and financial accessibility for MBR. The policy evaluation revealed that apparatus resources, institutions, infrastructure and technology, finance, and regulations play an important role in the management of RUSUNAWA. Key findings include the need to improve the skills and knowledge of officials, improve public facilities, and provide social assistance to ease the financial burden of residents. With continuous evaluation, it is expected that the RUSUNAWA program can be more effective in improving the quality of life of low-income people in Sukabumi.